Comparison of a new sublingual sedation troche with midazolam, ketamine, and ondansetron with intravenous sedation and the effects on vital signs. Issue 7 (July 2020) - Dickson, Drew; Padilla Conde, Tania; Berdahl, James; Osmundson, Greg; Sudhagoni, Ramu; Bender, Chris; Thompson, Vance; Berdahl, John
Abstract : Purpose: To compare effects of the MKO Melt (midazolam 3 mg, ketamine 25 mg, and ondansetron 2 mg) with intravenous (IV) sedation on vital signs of patients who underwent cataract surgery. Setting: Two private ophthalmology practices in Sioux Falls, South Dakota, USA. Design: Retrospective analysis. Methods: Preoperative, intraoperative, and postoperative vital signs were compared between individuals who underwent cataract surgery and received exclusively either MKO (n = 991) or traditional IV methods (n = 120) for sedation. Clinical significance was defined as a 5 mm Hg change in blood pressure, 3 beats per minute (bpm) change in heart rate, a change of 2 respirations per minute, or a change of 3% in O2 saturation. MKO Melt but not IV sedation was given before the reported preoperative vital signs. Results: There were 1111 patients included in this study. Preoperative systolic blood pressure (SBP) was 133.7 ± 15.6 mm Hg in the MKO group and 139.6 ± 17.3 mm Hg in the IV group ( P = .0001). Postoperative SBP was 130.8 ± 12.9 mm Hg in the MKO group and 135.8 ± 19.3 mm Hg in the IV group ( P < .01). Postoperative heart rate was 66.3 ± 10.4 bpm in the MKO group compared with 69.8 ± 10.5 bpm in the IV group ( P < .001). No other clinically and statistically significant differences were found. The mean number of melts used was 1.5. Conclusions: Clinically and statistically significant improvements in preoperative and postoperative SBP and postoperative heart rate were observed in patients who received MKO Melt. The MKO Melt was safe, effective, and well tolerated and a viable alternative to IV sedation.